Fasciola gigantica التغيرات المرضية الناجمة عن تغذية الفئران المختبرية على أكباد الجاموس المصابة بطفيلي - إسماعيل خليل, منال (University of Thi-Qar Journal of Science, 2010)
The present study has proven that the livers of infected animals by Fasciola gigantica should not be addible for human being in even they cooked.The present study involved use of (treated and untreated with heat) liver squash of infected Buffalo with F. gigantica, the results showed that feeding on infected livers caused congestion and increase in number of Kuffer‘s Cells in blood vessels in dosing mice with liver squash treated with heat.The study revealed also congestion of blood vessels and sinusoids, in addition to aggregation of Kuffer‘s Cells beside blood vessels and increase in their number and hyperpigmentation of nuclei as well as enlargement of liver cells in the mice administered with liver squash untreated with heat.